Strategy of Akidah Akhlak Teachers in Improving the Morals of Generation-Z Students at MTs Walisongo Pecangaan Jepara - Azizah, Azizah (Al Hikmah: Journal of Education, 2022)
The rapid flow of globalization has an influence on technological developments, thus giving birth to a new generation, namely Generation Z who have known technology since birth. It also has an impact on moral decadence or the decline in student morale which is currently being felt in the world of education. Teachers play an important role in efforts to improve student morale. Therefore, the objectives of this study are: 1) to find out the strategy of akidah moral teachers in improving the morale of generation Z students at MTs Walisongo Pecangaan Jepara, 2) to evaluate the strategies of teachers of aqidah morality in improving the morale of generation Z students at MTs Walisongo Pecangaan Jepara, and 3) to identify the supporting factors and inhibiting factors of the strategy of the moral aqidah teacher in improving the morale of generation Z students at MTs Walisongo Pecangaan Jepara. This research method is descriptive qualitative using interview and observation approach. The results of the study show that the strategies that have been applied by moral aqidah teachers such as school rules, habituation strategies, giving advice and motivation, giving sanctions, etc. have a positive influence on increasing student morale. as for the supporting factors, namely support from parents and the family environment, socio-cultural aspects in the school environment, school leaders including teachers and school infrastructure. Meanwhile, the inhibiting factors are the negative influence of the Internet, lack of attention from parents and families, different environmental conditions of students, and limited time.